Vertically aligned carbon nanotubes synthesized from waste chicken fat - Suriani, A.B.; Dalila, A.R.; Mohamed, A.; Mamat, M.H.; Salina, M.; Rosmi, M.S.; Rosly, J.; Md Nor, R.; Rusop, M. (2013)
For the first time, vertically aligned carbon nanotubes (VACNTs) have been successfully synthesized using waste chicken fat as the starting material. Chicken fat oil, which was obtained through a rendering process, was directly mixed with 5.33 wt ferrocene as a catalyst to form the synthesis stock. A mixture of single- and multi-walled VACNTs was synthesized at a fixed temperature of 750 Â°C in a thermal chemical vapour deposition furnace. Field emission scanning electron microscopy, micro-Raman spectroscopy and thermogravimetric analyses showed that the produced VACNTs were of excellent quality, comparable to those obtained using conventional carbon sources, with a purity of 88.2 and tube diameters ranging from 18 to 78 nm. Based on our study, waste chicken fat is a promising carbon source for the synthesis of high-quality and high-purity VACNTs. Â© 2013 Elsevier B.V. All rights reserved.